Strategi pemasaran digital scarlett whitening - Atika Dian Puspita; Devi Desrianti; Nur Anisa Amania; Erwin Permana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The current development of various marketing media means that business actors must be able to execute marketing strategies in various media channels, both directly and digitally. One product that utilizes all communication channels to market its products is Scarlett Whitening. Although it is classified as a new brand, it is already quite popular among Indonesian people. This study aims to analyze the digital marketing strategy for Scarlett Whitening products. The research was conducted with a descriptive qualitative approach. Research data uses primary data and secondary data. Data is collected by making observations while secondary data comes from the results of searching data in various popular and official databases, as well as scientific publications. The results of the study concluded that there were four main digital strategies carried out by the company, namely Collaboration with Influencers, providing Platforms and marketing on various marketplaces such as Lazada, Tokopedia, Tiktok Shop and Shopee, making brand ambassadors not only local but also foreign actors who have many fans and implementing promotional strategies such as flash sales, promos in the form of Scarlett Whitening beauty product packages and discounts. This research suggests carrying out marketing innovations in addition to maintaining existing digital marketing strategies. The marketing innovation carried out is collaborative marketing with various well-known products. If this research examines marketing strategy in general, then for future researchers this research suggests conducting research on more specific strategy analysis, for example marketing analysis using influencers. Specific research is expected to produce more in-depth results.